Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum Dan Belanja Modal Terhadap Tingkat Kemandirian Keuangan Daerah - Shinta Bella (Jurnal Syntax Transformation, 2022)
This paper aims to determine how much influence the Regional Original Income, communication and capital expenditures, jointly and partially have on the Provision of Incentives. The research variables are Regional Original Income (X1), General Allocation Funds (X2), Capital Expenditures (X3), and Level of Financial Independence (Y). Methods of collecting data through surveys and distributing questionnaires. The analytical method used is the classical assumption test and the Regression Estimation of the Panel Data Model, then based on the partial test (t test) obtained: (a) Regional Original Income has a positive and significant effect on the level of financial independence. (b) The general allocation fund has a positive and significant effect on the level of financial independence. (c) Capital expenditure is positive and significant to the level of financial independence. Then based on the joint hypothesis test (Test F) it can be seen that Regional Original Income, General Allocation Funds and Capital Expenditures, have a positive and significant effect on the Level of Financial Independence. Finally, the writing team suggests that the Regency and City Governments throughout the Province of West Sumatra can pay attention and improve in terms of Regional Original Income, General Allocation Funds and Capital Expenditures, on the Level of Financial Independence in order to increase the Level of Financial Independence.